Inhibition of Biofilm Formation and Related Gene Expression of Listeria monocytogenes in Response to Four Natural Antimicrobial Compounds and Sodium Hypochlorite - Liu, Yunge; Wu, Lina; Han, Jina; Dong, Pengcheng; Luo, Xin; Zhang, Yimin; Zhu, Lixian (Frontiers in Microbiology, 2021)
The aim of this study was to assess the efficacy of four natural antimicrobial compounds (cinnamaldehyde, eugenol, resveratrol and thymoquinone) plus a control chemical disinfectant (sodium hypochlorite) in inhibiting biofilm formation by Listeria monocytogenes CMCC54004 (Lm 54004) at a minimum inhibitory concentration (MIC) and sub-MICs. Crystal violet staining assay and microscopic examination were employed to investigate anti-biofilm effects of the evaluated compounds, and a real-time PCR assay was used to investigate the expression of critical genes by Lm 54004 biofilm. The results showed that five antimicrobial compounds inhibited Lm 54004 biofilm formation in a dose dependent way. Specifically, cinnamaldehyde and resveratrol showed better anti-biofilm effects at 1/4 × MIC, while sodium hypochlorite exhibited the lowest inhibitory rates. A swimming assay confirmed that natural compounds at sub-MICs suppressed Lm 54004 motility to a low degree. Supporting these findings, expression analysis showed that all four natural compounds at 1/4 × MIC significantly down-regulated quorum sensing genes (agrA, agrC, and agrD) rather than suppressing the motility- and flagella-associated genes (degU, motB, and flaA). This study revealed that sub-MICs of natural antimicrobial compounds reduced biofilm formation by suppressing the quorum sensing system rather than by inhibiting flagella formation.